Service Quality Aspects in Ferry Passenger Transport - Examples from Norway - Mathisen, Terje Andreas; Solvoll, Gisle (European Journal of Transport and Infrastructure Research, 2010)
Changes in the level of service for scheduled passenger transport influence both operating costs and passengers’ generalised travel costs. This article focuses on the service level and service quality of ferry crossings using empirical data from a survey carried out in Norway in 2008. Using gap analysis we document how both enterprise and household ferry users rate the importance of and their current satisfaction with a number of service aspects concerning Norwegian ferries. Fares, discount schemes and sufficient capacity in the summer are rated as highly important but providing a low level of satisfaction by both user enterprise and household respondents. These elements should, therefore, be paid special attention to when adjusting the service level. The results from the survey are of special interest for the Norwegian transport authorities with respect to revisions of the national ferry service standard, and the survey method can provide a useful tool when evaluating transport initiatives.